The Influence of CEO Characteristics on Takeover Activity - Chirkowski, Adam (2008)
There is a large body of literature which seeks to explain the motives for takeover activity in the modern corporation, suggesting that it can be condensed to three factors; Agency, Synergy and Hubris. There is an even larger body of evidence which suggests such takeover activity is detrimental to the shareholder value of firms which partake in it, and therefore questions arise as to why such decisions are taken